Peran Generasi Muda dalam Keberlangsungan Pendidikan Islam - Asef Umar Fakhruddin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
This paper discussing the role of youth generation in Islamic education that tends to less giving development opportunity and creativity. Islamic education was only as training which the main target explaining about theory, but lack of real action. Thereâ€™s madrasah education model, to realize madrasah as academic excellence as public school, plus Islamic specialty. There also dormitory education model, and â€œ Plusâ€ school phenomenon. Exactly, now many more Islamic school Plus that progressing more than public school. In Islam, problem of discipline, working ethos, motivation, and achievement occupy the very important role. Here youth strength:readiness to learn, active sharing in compiling best framework for the world of Islam education in this country. This youth people will be able to do the reform and create the new formulation to Islam education.